Antemortem vitreous potassium may strengthen postmortem interval estimates. (June 2016) - Kokavec, Jan; Min, San H.; Tan, Mei H.; Gilhotra, Jagjit S.; Newland, Henry S.; Durkin, Shane R.; Casson, Robert J.
Highlights: Several studies report a relationship between PMI and vitreous solute concentration. To date, these expressions have not utilised data for when PMI = 0. Calibration against the antemortem vitreous concentrations may improve accuracy. We have reported the antemortem vitreous concentrations of 15 analytes, including potassium. Abstract: The purpose of this letter is to highlight that postmortem interval estimates using vitreous potassium concentrations may be further optimised by calibration against antemortem vitreous samples.